MATURE FIELD AND WELL REVITALIZATION: WELL CANDIDATE SCREENING FOR MATRIX ACIDIZING - Felix Turnip, Jon
The research is motivated by the notable decline in production observed in mature fields in Indonesia. This decline can be attributed to various factors, including reservoir heterogeneity, resulting in uneven distribution of fluids and pressure within the reservoir. Well stimulation has emerged as a promising solution to enhance the production capability of individual wells. One such method is Matrix Acidizing, which involves injecting acid into the formation to dissolve minerals and improve permeability near the wellbore. Prior to implementing Matrix Acidizing, a thorough screening process is essential to enhance the likelihood of success and optimize operational efficiency. The primary objective of this paper is to present a comprehensive workflow that identifies the most suitable candidates for Matrix Acidizing. The initial candidate selection is based on the fundamental concept of utilizing Heterogeneity Index (HI). Moreover, other pertinent parameters employed in the screening process include the Estimated Ultimate Recovery (EUR) of the wells. Subsequently, a short-list of wells selected for Matrix Acidizing undergoes nodal analysis, design process, and potential gain calculations to ascertain the anticipated outcomes of the stimulation procedure. The research findings indicate that all three selected wells out of the initial of 24 wells exhibited a substantial increase in production following the Matrix Acidizing stimulation. These results substantiate the proposition that the utilization of HI for well selection, in conjunction with Matrix Acidizing stimulation, can effectively enhance well productivity in mature oil fields in Indonesia.